2017
DOI: 10.1111/jpi.12428
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin delays photoreceptor degeneration in a mouse model of autosomal recessive retinitis pigmentosa

Abstract: Retinitis pigmentosa (RP) comprises a group of incurable inherited retinal degenerations. Targeting common processes, instead of mutation-specific treatment, has proven to be an innovative strategy to combat debilitating retinal degeneration. Growing evidence indicates that melatonin possesses a potent activity against neurodegenerative disorders by mitigating cell damage associated with apoptosis and inflammation. Given the pleiotropic role of melatonin in central nervous system, the aim of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 66 publications
(91 reference statements)
0
17
0
Order By: Relevance
“…Finally, melatonin drives the modulation of rod dark adaptation and thus it potentially protects the retina from light-induced damage during the day. 110 Consistently with these experimental findings, several studies have shown that administration of exogenous melatonin can protect photoreceptors from apoptosis in mouse models of retinitis pigmentosa 111 , 112 and that melatonin signaling is involved in the modulation of rod and cone photoreceptor viability during aging. 113 , 114 A protective effect of melatonin on photoreceptor cells has been also observed in humans since administration of exogenous melatonin (3 mg) delayed the progression of age related macular degeneration (AMD) in a few patients.…”
Section: Circadian Clocks and Visual Functionmentioning
confidence: 60%
“…Finally, melatonin drives the modulation of rod dark adaptation and thus it potentially protects the retina from light-induced damage during the day. 110 Consistently with these experimental findings, several studies have shown that administration of exogenous melatonin can protect photoreceptors from apoptosis in mouse models of retinitis pigmentosa 111 , 112 and that melatonin signaling is involved in the modulation of rod and cone photoreceptor viability during aging. 113 , 114 A protective effect of melatonin on photoreceptor cells has been also observed in humans since administration of exogenous melatonin (3 mg) delayed the progression of age related macular degeneration (AMD) in a few patients.…”
Section: Circadian Clocks and Visual Functionmentioning
confidence: 60%
“…For P23H rats carrying a mutation defect, adding melatonin into the drinking water alleviates the photoreceptors loss and visual impairments (Lax et al, 2011). Daily injection of melatonin also retards the photoreceptor degeneration in the rd10 and rds mice (Liang et al, 2001;Xu et al, 2017). More excitingly, a clinical investigation shows that the age-related macular degeneration (AMD) patients have lower melatonin level, and the oral melatonin supplements delay the macular degeneration and improve the visual acuity of these patients (Crooke et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of microglial activation and cytokine release has been shown to reduce photoreceptor cell death [ 107 , 108 ]. Down-regulation of pathways involved in innate immunity and inflammation were also found to reduce retinal degeneration and preserve photoreceptor function in Rho P347S mice [ 109 ].…”
Section: Recruitment and Activation Of Microglia And Monocytesmentioning
confidence: 99%